Growing up in Yoknapatawpha: Race, Code/s and the Loss of Innocence in William Faulkner’s Short Stories - Bubíková, Šárka (My University, 2019)
This paper discusses William Faulkner’s complex literary representations of childhood in some of his short stories. In mid-1930s, Faulkner published several short stories focusing on the coming-of-age and loss of innocence. While earlier critics interpreted Faulkner’s treatment of a loss as typically modernist, later it was emphasized that the myth of antebellum South and the Jim Crow reality play a key role. However, even if race is significant in the coming-of-age of Faulkner’s characters, it is not the sole defining factor. Youth in the Faulknerian world of the Yoknapatawpha county struggles with conflicting demands of tradition and individual inclination, limitations and expectations arising from existing codes –the Southern code of honor and the Christian moral code – as well as a lack of these in times of upheaval. While Faulkner places his child characters in a particular historical era and thinly veiled specific location, he also addresses some of the most common, general, or in a way existential aspects of childhood, such as peer relationships, struggles with authority, and loss of innocence.
Dětství v okrese Yoknapatawpha: Rasa, etiketa a ztráta nevinnosti v povídkách Williama Faulknera
Keywords: William Faulkner; short story; race; Southern code of honor; childhood; loss of innocence; The Unvanquished; William Faulkner; povídky; dětství; rasa; ztráta nevinnosti; jižanská čest; Nepřemožitelní